Persistent Lactatemia in Mauriac Syndrome - Nada El Tobgy; Laura Hinz (Case Reports in Endocrinology)
Mauriac syndrome is a rare disorder that occurs in patients with type 1 diabetes mellitus (T1DM) with glucose levels significantly above target, characterized by hepatomegaly, growth delay, and cushingoid features. Another distinguishing feature of Mauriac syndrome is persistent lactatemia during diabetic ketoacidosis (DKA) management. We present a case of an 18-year-old patient with T1DM who presented in DKA and then developed elevated lactate levels leading to a diagnosis of Mauriac syndrome. The cause of the persistent lactatemia is not well understood though it is likely related to glycogenic hepatopathy causing hepatomegaly, abnormalities in glucose metabolism, and subsequent inappropriate lactate production. Since the liver changes seen in Mauriac syndrome are reversible with optimal blood glucose control, these patients should be connected to intensive psychosocial and medical support to help them improve their blood glucose levels.